The best man's problem - Taíno, Sera (Harlequin special edition, 2023)
He can't forget the kiss he shared with the best man. But is he the best man for him? His sister's wedding isn't the ideal place for Rafael Navarro to reconnect with the man he kissed in a moment of reckless abandon. But it's impossible to avoid best man Étienne Galois! The gorgeous Haitian photographer hasn't forgotten the intimate moment they shared, even if Rafi is the most maddening person he's ever met. Can the two find common ground, proving opposites not only attract--they can become lovers for life?